Application of neural networks in prediction of enterprise development in global environment - Parkhomenko, Nataliia Oleksandrivna; Otenko, Iryna Pavlivna; Martynovych, Nataliia Oleksandrivna; Otenko, Vasyl Ivanovych (SCMS Journal of Indian Management, 2023)
This paper deals with the issue of prediction models of enterprise development in the global environment and the development strategy formation of the enterprise. The paper aims at using neural networks to assess the current and forecast the future state of enterprises and to propose the optimum development strategy for a different area of business. The research also used the methods of multiple regression to evaluate the correlation between initial features and general factors, which in our case are global and national development indicators. The results of the analysis were used for building a model of business systems development in Statistica 13.5 program. The model, based on selected indicators, identifies the current state of the enterprise and future development strategies and designs the optimum scenario and proposes its development for the long-term progress of the enterprise. This approach to prediction is applicable to global and domestic companies

Стаття присвячена прогнозним моделям розвитку підприємства в глобальному середовищі та формуванню стратегії розвитку підприємства. Запропоновано використання нейронних мереж для оцінки поточного і прогнозування майбутнього стану на засадах чого сформовано оптимальну стратегію розвитку для окремої сфери діяльності бізнес. У дослідженні також використовувалися методи множинної регресії для оцінки кореляції між вихідними ознаками і фактори, якими в нашому випадку є глобальні та національні показники розвитку. Результати аналізу використано при побудови моделі розвитку бізнес-систем у програмі Statistica 13.5. Модель відображає поточний стан підприємства та сценарії майбутньої стратегії довгострокового розвитку підприємства.
Keywords: prediction; enterprise development; global environment; neural networks; development strategy; global and national development indicators; прогнозування; розвиток підприємства; глобальне середовище; нейронні мережі; стратегія розвитку; глобальне і показники національного розвитку